NORMATIVE POWER OF THE EC DIRECTIVES - K. Khaliev (Russian Journal of Economics and Law)
The article gives the detailed explanation of the normative power of legal acts accepted by such organizations as Euro Parliament, Euro Commission, European Community Court, etc. The author also gives the characteristics of the special Protocol on subsidiary and ratability principles accepted by Euro Commission.